Intelligent air-cushion system of swamp peat vehicle control: fuzzy logic technique - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (2009)
Focusing on optimizing the total power consumption of the vehicle, two main issues were studied in this paper. First, a theoretical model is developed to minimize total power consumption of the vehicle. Second, a control scheme is proposed to achieve the control targets and to minimize the power consumption by using a fuzzy logic controller. Compared with traditional approach, fuzzy logic approach is more efficient for the representation, manipulation and utilization. Therefore, the primary purpose of this work was to investigate the relationship between total power consumption, clearance height and cushion pressure, and to illustrate how fuzzy logic technique might play an important role in prediction of total power consumption. All experimental values were collected from the field test using a developed prototype hybrid electrical air-cushion tracked vehicle.